FIQH PENDIDIKAN DALAM PERSPEKTIF KLASIK DAN MODERN - Mhd. Maulana Ansori; Chanifudin (EL-TA’DIB: Journal of Islamic Education, 2025)
This article discusses educational fiqh from classical and modern perspectives as a normative framework that guides the practice of Islamic education. This study aims to analyze the basic concepts of educational fiqh, the characteristics of classical and modern thought, and their implications for contemporary Islamic educational practice. Using a qualitative approach using library research methods, this article examines primary and secondary sources relevant to the theme of Islamic fiqh and education. The results of the study indicate that classical educational fiqh emphasizes normative, ethical, and transcendental aspects with an orientation toward the formation of morals and scientific etiquette. Meanwhile, modern educational fiqh develops contextually with a maqāṣid al-syarī‘ah approach, integrative, and responsive to the challenges of the times. A comparative analysis reveals that the two perspectives are complementary. Therefore, the future development of educational fiqh needs to integrate classical values ​​with a modern approach so that Islamic education remains relevant, just, and oriented towards the welfare of the community. Keywords: Educational fiqh, Islamic education, Classical perspective, Modern perspective, Maqāṣid al-syarī‘ah.